Struktura, zmiany organizacyjne i poziom nauczania Publicznej Szkoły Powszechnej w Brdowie w latach 1919–1939 - Racinowski, Dariusz (Biuletyn Historii Wychowania, 2017)
The school in Brdów dates back to the mid–15th century. It was founded and managed by Pauline fathers. In the following centuries, the school functioned with varying degrees of success. The realdevelopment of the Brdów school occurred in the interwar period. In the following years, the structure of the school changed, due to the growing number of students. Before the outbreak of World War II, there was a general public school of 3rd level, i.e. one with seven grades, in Brdów. The teachers worked under very difficult conditions. The school building was too small to accommodate all the classes. The classrooms were overcrowded. However, the educators tried to achieve the best results possible. This was confirmed by subsequent inspections conducted by educational authorities. Just before the outbreak of World War II, a new school building was opened in Brdów which greatly improved working and learning conditions there.